Performance of a highly successful outbreak strain of Mycobacterium tuberculosis in a multifaceted approach to bacterial fitness assessment - Yokobori, Noemí (2018)
Determining bacterial fitness represents a major challenge and no single parameter can accurately predict the ability of a certain pathogen to succeed. The M strain of Mycobacterium tuberculosis managed to spread and establish in the community and caused the largest multidrug-resistant tuberculosis outbreak in Latin America. We have previously shown that the M strain can manipulate the host immune response, but we still have no direct evidence, other than epidemiology, that can account for the enhanced fitness of the M strain. Our objective was to further characterize the performance of the outbreak strain M in different fitness assays. Two main aspects were evaluated: (1) molecular characterization of selected isolates from the M outbreak and related strains and (2) comparative fitness and in vivo performance of representative M strain isolates vs. the non-prosperous M strain variant 410. Our approach confirmed the multifaceted nature of fitness. Altogether, we conclude that the epidemiologically abortive strain 410 was vulnerable to drug-driven pressure, a weak competitor, and a stronger inductor of protective response in vivo. Conversely, the isolate 6548, representative of the M outbreak peak, had a growth disadvantage but performed very well in competition and induced lung damage at advanced stages in spite of reaching relatively low CFU counts. Integration of these observations supports the idea that the M strain managed to find a unique path to success.